Ecological and economic outcomes of area-based conservation and sustainable fisheries management in the Mediterranean Sea - M. D. Castro-Cadenas; J. Claudet; M. Ortega; V. Sbragaglia; M. Coll (Reviews in Fish Biology and Fisheries, 2026)
Intergovernmental targets are reinforcing the need for more sustainable fisheries and more effective marine conservation. It is now urgent to understand how area-based conservation and sustainable fisheries management tools contribute to these environmental and socio-economic goals. Here, we systematically reviewed and assessed the outcomes of marine protected areas (accounting for their level of protection and of enforcement), fisheries restricted areas, and fishing effort reduction measures in the Mediterranean Sea, using 11 ecological and economic indicators. We show that commercial species in general, and fish species in particular, showed the highest proportion of positive to neutral effects in response to the management tools assessed compared to non-commercial and benthic assemblages. Among the management tools, partially protected areas showed the lowest proportion of positive to neutral effects compared to fully protected areas, and to the other management tools. Partially protected areas and fully protected areas showed higher neutral to negative ratio than fishing effort reduction measures overall. Within MPA protection levels with high enforcement, fully protected areas outperformed minimally protected areas, based on the higher positive to neutral effects ratio. Our results further underscored the critical role of enforcement, particularly for fully protected areas, which were found more beneficial overall under high enforcement than medium enforcement (based on positive to neutral effects ratio). Our findings support the prioritisation of well enforced fully protected areas and the integration of fisheries management and conservation objectives in marine spatial planning to effectively achieve regional and global sustainability goals for the ocean.

Pan-continental assessment of socioeconomic and environmental predictors of PFAS occurrence in European rivers from a harmonised monitoring study - Jun Li; Alistair B.A. Boxall; Caroline Swan; Selwyn Hoeks; Racliffe W.S. Lai; John L. Wilkinson; Recep C. Altinbag; Åsa Arrhenius; Roman Ashauer; Thomas Backhaus; Besnik Baraj; Vasiliki G. Beretsou; et al. (Water Research, 2026)

Effect of aging on the release of additives and the toxicity of microplastics - Alicia Sánchez; Sara Exojo-Trujillo; Diego Ríos; José M. Coll; Mar Masia-Santonja; Dinoraz Vélez; Vicenta Devesa (Environmental Toxicology and Pharmacology, 2026)

What happened with the smaller ones? First comprehensive taphonomic analysis of microvertebrates from the Late Pleistocene of Rancho La Brea (Los Angeles, USA) - Fernando J. Fernández; Claudia I. Montalvo; M. Dolores Marin‐Monfort; Renata Sostillo; Daiana G. Coll; Emily Lindsey; Karin A. Rice; Gary T. Takeuchi; Rodrigo L. Tomassini (Journal of Quaternary Science, 2025)
Rancho La Brea (RLB) in Los Angeles, USA, is an iconic fossil locality, owing to the high number and diversity of Quaternary vertebrate remains and their excellent preservation. More than a century of study, focused predominantly on large mammals, has provided valuable information along different lines of research, including taxonomy, taphonomy, isotopic ecology, functional morphology, and paleopathology. In order to develop a better understanding of the formation of this site, we conducted a taphonomic study of the microvertebrates, using samples from asphalt seeps dating to before the Last Glacial Maximum. The taphonomic evidence suggests that direct entrapment is the most plausible process to explain the primary accumulation of the thousands of microvertebrate remains. Based on the absence of digestive corrosion and feeding marks, low percentages of juvenile individuals, relative abundance patterns, and anatomical indices (postcranial elements vs. cranial elements and distal vs. proximal limb elements), the activity of predators/scavengers is ruled out as a primary process in producing the assemblages, although other processes, such as water transport of skeletal elements from nearby areas, could also have played a role in the formation of the deposits. The occurrence of successive entrapments and episodes of fluvial transportation, combined with post‐depositional internal movement within the seeps, would have given rise to the development of time‐averaged assemblages produced through a complex interplay of factors.

Priorities assessment in a marine protected area: The case of the Northeast of Mallorca - J.J. Martín-Estarellas; M. Ortega; M. Coll (Fisheries Research, 2025)

Assessing target areas for precipitating moisture source analysis of extratropical cyclones: An analysis based on case studies - Patricia Coll-Hidalgo; Raquel Nieto; Albenis Pérez-Alarcón; Ricardo M. Trigo; Jose Carlos Fernández-Alvarez; Luis Gimeno (Atmospheric Research, 2024)

CyTRACK: An open-source and user-friendly python toolbox for detecting and tracking cyclones - Albenis Pérez-Alarcón; Patricia Coll-Hidalgo; Ricardo M. Trigo; Raquel Nieto; Luis Gimeno (Environmental Modelling & Software, 2024)

Spatial patterns of β-diversity under cumulative pressures in the Western Mediterranean Sea - M. Grazia Pennino; Juan Pablo Zurano; Manuel Hidalgo; Antonio Esteban; Carlos Veloy; José M. Bellido; Marta Coll (Marine Environmental Research, 2024)

Future climate‐induced distribution shifts in a sexually dimorphic key predator of the Southern Ocean - Jazel Ouled‐Cheikh; David March; Renato Borras‐Chavez; Massimiliano Drago; Michael E. Goebel; José M. Fariña; Manel Gazo; Marta Coll; Luis Cardona (Global Change Biology, 2024)
The response to climate change in highly dimorphic species can be hindered by differences between sexes in habitat preferences and movement patterns. The Antarctic fur seal, Arctocephalus gazella , is the most abundant pinniped in the Southern Hemisphere, and one of the main consumers of Antarctic krill, Euphausia superba , in the Southern Ocean. However, the populations breeding in the Atlantic Southern Ocean are decreasing, partly due to global warming. Male and female Antarctic fur seals differ greatly in body size and foraging ecology, and little is known about their sex‐specific responses to climate change. We used satellite tracking data and Earth System Models to predict changes in habitat suitability for male and female Antarctic fur seals from the Western Antarctic Peninsula under different climate change scenarios. Under the most extreme scenario (SSP5‐8.5; global average temperature +4.4°C projected by 2100), suitable habitat patches will shift southward during the non‐breeding season, leading to a minor overall habitat loss. The impact will be more pronounced for females than for males. The reduction of winter foraging grounds might decrease the survival of post‐weaned females, reducing recruitment and jeopardizing population viability. During the breeding season, when males fast on land, suitable foraging grounds for females off the South Shetland Islands will remain largely unmodified, and new ones will emerge in the Bellingshausen Sea. As Antarctic fur seals are income breeders, the foraging grounds of females should be reasonably close to the breeding colony. As a result, the new suitable foraging grounds will be useful for females only if nearby beaches currently covered by sea ice emerge by the end of the century. Furthermore, the colonization of these new, ice‐free breeding locations might be limited by strong female philopatry. These results should be considered when managing the fisheries of Antarctic krill in the Southern Ocean.

Current Trends and Future Directions in Urban Social Prescribing - J. S. Litt; L. Coll-Planas; A. L. Sachs; M. Masó Aguado; M. Howarth (Current Environmental Health Reports, 2023)

Climatological variations of moisture sources for precipitation of North Atlantic tropical cyclones linked to their tracks - Albenis Pérez-Alarcón; Patricia Coll-Hidalgo; José C. Fernández-Alvarez; Ricardo M. Trigo; Raquel Nieto; Luis Gimeno (Atmospheric Research, 2023)

Metals, pesticides, and emerging contaminants on water bodies from agricultural areas and the effects on a native amphibian - Julieta Peluso; Agostina Martínez Chehda; Melisa S. Olivelli; Federico M. Ivanic; Cristina S. Pérez Coll; Florencia Gonzalez; Lautaro Valenzuela; Dante Rojas; Diego Cristos; Matías Butler; Roberto J. Candal; Carolina M. Aronzon (Environmental Research, 2023)

Innate immune response of rainbow trout erythrocytes to spinycterins expressing a downsized viral fragment of viral haemorrhagic septicaemia virus - S. Puente-Marin; D. Cazorla; V. Chico; J. Coll; M. Ortega-Villaizan (Aquaculture, 2023)

The Effect of Mindfulness-based Programs on Cognitive Function in Adults: A Systematic Review and Meta-analysis - Tim Whitfield; Thorsten Barnhofer; Rebecca Acabchuk; Avi Cohen; Michael Lee; Marco Schlosser; Eider M. Arenaza-Urquijo; Adriana Böttcher; Willoughby Britton; Nina Coll-Padros; Fabienne Collette; Gaël Chételat; et al. (Neuropsychology Review, 2022)
Mindfulness-based programs (MBPs) are increasingly utilized to improve mental health. Interest in the putative effects of MBPs on cognitive function is also growing. This is the first meta-analysis of objective cognitive outcomes across multiple domains from randomized MBP studies of adults. Seven databases were systematically searched to January 2020. Fifty-six unique studies ( n = 2,931) were included, of which 45 ( n = 2,238) were synthesized using robust variance estimation meta-analysis. Meta-regression and subgroup analyses evaluated moderators. Pooling data across cognitive domains, the summary effect size for all studies favored MBPs over comparators and was small in magnitude ( g = 0.15; [0.05, 0.24]). Across subgroup analyses of individual cognitive domains/subdomains, MBPs outperformed comparators for executive function ( g = 0.15; [0.02, 0.27]) and working memory outcomes ( g = 0.23; [0.11, 0.36]) only. Subgroup analyses identified significant effects for studies of non-clinical samples, as well as for adults aged over 60. Across all studies, MBPs outperformed inactive, but not active comparators. Limitations include the primarily unclear within-study risk of bias (only a minority of studies were considered low risk), and that statistical constraints rendered some p -values unreliable. Together, results partially corroborate the hypothesized link between mindfulness practices and cognitive performance. This review was registered with PROSPERO [CRD42018100904].

Synergistic effects of glyphosate- and 2,4-D-based pesticides mixtures on Rhinella arenarum larvae - Julieta Peluso; Agustina Furió Lanuza; Cristina S. Pérez Coll; Carolina M. Aronzon (Environmental Science and Pollution Research, 2022)

Current and Future Influence of Environmental Factors on Small Pelagic Fish Distributions in the Northwestern Mediterranean Sea - Maria Grazia Pennino; Marta Coll; Marta Albo-Puigserver; Elena Fernández-Corredor; Jeroen Steenbeek; Ana Giráldez; María González; Antonio Esteban; José M. Bellido (Frontiers in Marine Science, 2020)

Contrasting patterns of tree species mixture effects on wood δ13C along an environmental gradient - G. de Streel; C. Collet; I. Barbeito; K. Bielak; A. Bravo-Oviedo; G. Brazaitis; L. Coll; L. Drössler; D. Forrester; M. Heym; M. Löf; M. Pach; et al. (European Journal of Forest Research, 2020)

Advances and challenges in modelling the impacts of invasive alien species on aquatic ecosystems - X. Corrales; S. Katsanevakis; M. Coll; J. J. Heymans; C. Piroddi; E. Ofir; G. Gal (Biological Invasions, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Identification of new viral variants specific to the honey bee mite Varroa destructor - Salvador Herrero; Anabel Millán-Leiva; Sandra Coll; Rosa M. González-Martínez; Stefano Parenti; Joel González-Cabrera (Experimental and Applied Acarology, 2019)

Brassinosteroids promote growth, fruit quality and protection against Botrytis on Fragaria x ananassa - R. N. Furio; S. M. Salazar; G. M. Martínez-Zamora; Y. Coll; V. Hael-Conrad; J. C. Díaz-Ricci (European Journal of Plant Pathology, 2019)

Lynx eats cat: disease risk assessment during an Iberian lynx intraguild predation - F. Nájera; S. Sánchez-Cuerda; G. López; T. Del Rey-Wamba; C. Rueda; N. Vallverdú-Coll; J. Panadero; M. J. Palacios; J. V. López-Bao; J. Jiménez (European Journal of Wildlife Research, 2019)

Effect of natural and synthetic Brassinosteroids on strawberry immune response against Colletotrichum acutatum - R. N. Furio; P. L. Albornoz; Y. Coll; G. M. Martínez Zamora; S. M. Salazar; G. G. Martos; J. C. Díaz Ricci (European Journal of Plant Pathology, 2019)

Photo‐identification as a tool to study small‐spotted catshark Scyliorhinus canicula - J. Navarro; A. Perezgrueso; C. Barría; M. Coll (Journal of Fish Biology, 2018)
Photo‐identification (photo‐ID) was tested as a means to identify individual small‐spotted catsharks Scyliorhinus canicula . The spotting pattern of the caudal region of S. canicula was used for the tests and revealed that photo‐ID is an efficient method to identify individuals. Photo‐ID is logistically simple, making it a potential alternative to traditional tagging to provide information on the distribution patterns and population dynamics of S. canicula and related species.

Front Cover - Aitor Ameztegui; Lluís Coll; Lluís Brotons; Josep M. Ninot (Global Ecology and Biogeography, 2018)

Human diet and the chronology of neolithic societies in the north-east of the Iberian Peninsula: the necropolises of Puig d’en Roca and Can Gelats (Girona, Spain) - Juan F. Gibaja; Maria Fontanals-Coll; Stephanie Dubosq; F. Xavier Oms; Anna Augé; Francisco Javier Santos; Berta Morell; M. Eulàlia Subirà (Archaeological and Anthropological Sciences, 2017)

Strong fisheries management and governance positively impact ecosystem status - Alida Bundy; Ratana Chuenpagdee; Jennifer L Boldt; Maria de Fatima Borges; Mohamed Lamine Camara; Marta Coll; Ibrahima Diallo; Clive Fox; Elizabeth A Fulton; Ayse Gazihan; Astrid Jarre; Didier Jouffre; et al. (Fish and Fisheries, 2017)
Fisheries have had major negative impacts on marine ecosystems, and effective fisheries management and governance are needed to achieve sustainable fisheries, biodiversity conservation goals and thus good ecosystem status. To date, the IndiSeas programme (Indicators for the Seas) has focussed on assessing the ecological impacts of fishing at the ecosystem scale using ecological indicators. Here, we explore fisheries ‘Management Effectiveness’ and ‘Governance Quality’ and relate this to ecosystem health and status. We developed a dedicated expert survey, focused at the ecosystem level, with a series of questions addressing aspects of management and governance, from an ecosystem‐based perspective, using objective and evidence‐based criteria. The survey was completed by ecosystem experts (managers and scientists) and results analysed using ranking and multivariate methods. Results were further examined for selected ecosystems, using expert knowledge, to explore the overall findings in greater depth. Higher scores for ‘Management Effectiveness’ and ‘Governance Quality’ were significantly and positively related to ecosystems with better ecological status. Key factors that point to success in delivering fisheries and conservation objectives were as follows: the use of reference points for management, frequent review of stock assessments, whether Illegal, Unreported and Unregulated ( IUU ) catches were being accounted for and addressed, and the inclusion of stakeholders. Additionally, we found that the implementation of a long‐term management plan, including economic and social dimensions of fisheries in exploited ecosystems, was a key factor in successful, sustainable fisheries management. Our results support the thesis that good ecosystem‐based management and governance, sustainable fisheries and healthy ecosystems go together.

Flower structure and developmental stages of the capitulum of Smallanthus sonchifolius (Asteraceae): reproductive implications - M. S. Ibañez; M. I. Mercado; M. V. Coll Aráoz; M. L. Zannier; A. Grau; G. I. Ponessa (Journal of Plant Research, 2017)

Ecosystem effects of invertebrate fisheries - Tyler D Eddy; Heike K Lotze; Elizabeth A Fulton; Marta Coll; Cameron H Ainsworth; Júlio Neves de Araújo; Catherine M Bulman; Alida Bundy; Villy Christensen; John C Field; Neil A Gribble; Mejs Hasan; et al. (Fish and Fisheries, 2017)
Since the 1950s, invertebrate fisheries catches have rapidly expanded globally to more than 10 million tonnes annually, with twice as many target species, and are now significant contributors to global seafood provision, export, trade and local livelihoods. Invertebrates play important and diverse functional roles in marine ecosystems, yet the ecosystem effects of their exploitation are poorly understood. Using 12 ecosystem models distributed worldwide, we analysed the trade‐offs of various invertebrate fisheries and their ecosystem effects as well as ecological indicators. Although less recognized for their contributions to marine food webs, our results show that the magnitude of trophic impacts of invertebrates on other species of commercial and conservation interest is comparable with those of forage fish. Generally, cephalopods showed the strongest ecosystem effects and were characterized by a strong top‐down predatory role. Lobster, and to a lesser extent, crabs, shrimp and prawns, also showed strong ecosystem effects, but at lower trophic levels. Benthic invertebrates, including epifauna and infauna, also showed considerable ecosystem effects, but with strong bottom‐up characteristics. In contrast, urchins, bivalves, and gastropods showed generally lower ecosystem effects in our simulations. Invertebrates also strongly contributed to benthic–pelagic coupling, with exploitation of benthic invertebrates impacting pelagic fishes and vice versa. Finally, on average, invertebrates produced maximum sustainable yield at lower levels of depletion (~45%) than forage fish (~65%), highlighting the need for management targets that avoid negative consequences for target species and marine ecosystems as a whole.

The amino-terminal domain of ORF149 of koi herpesvirus is preferentially targeted by IgM from carp populations surviving infection - F. Torrent; A. Villena; P. A. Lee; W. Fuchs; S. M. Bergmann; J. M. Coll (Archives of Virology, 2016)

Repeated exposure to vicarious pain alters electrocortical processing of pain expressions - Michel-Pierre Coll; Mathieu Grégoire; Kenneth M. Prkachin; Philip L. Jackson (Experimental Brain Research, 2016)

Noncoding RNAs in smooth muscle cell homeostasis: implications in phenotypic switch and vascular disorders - N. Coll-Bonfill; B. de la Cruz-Thea; M. V. Pisano; M. M. Musri (Pflügers Archiv - European Journal of Physiology, 2016)

Differences in the relative roles of environment, prey availability and human activity in the spatial distribution of two marine mesopredators living in highly exploited ecosystems - Joan Navarro; Laura Cardador; Ángel M. Fernández; José M. Bellido; Marta Coll (Journal of Biogeography, 2016)
Aim Identifying the main factors affecting the spatial distribution of marine predators is essential in order to evaluate their distribution patterns, predict the potential impact of human activities on their populations and design accurate management actions. This information is also valuable from a more general management perspective, as marine predators are often considered indicators of habitat quality. In this context, we aimed to determine the degree to which environmental features, prey availability and human activities interact and influence spatial distribution of two marine mesopredator elasmobranchs, the small‐spotted catshark ( Scyliorhinus canicula ) and the Mediterranean starry ray ( Raja asterias ), living in a highly human‐exploited environment. Location Mediterranean Sea. Methods With information obtained from an extended experimental survey, we investigated the relative importance of environmental variables, prey availability and human activities on the spatial distribution of the abundance, biomass and occurrence rate of these marine mesopredators using deviance partitioning analyses. Results Our results revealed that environmental variables were the most important factors explaining the spatial distribution of Mediterranean starry ray, whereas small‐spotted catshark distribution was also influenced by prey availability and human factors. From a management point of view, these findings suggest that Mediterranean starry ray could be a good candidate as an indicator species of demersal environmental quality. On the other hand, the distribution of the small‐spotted catshark, which responds in an interactive and complex way to environment, prey availability and particular human activities, may be misleading as an environmental indicator. Main conclusions The spatial distribution of elasmobranchs in highly human‐impacted marine areas can reflect the interactive and combined effects of multiple factors. To avoid misunderstandings, attention should be paid to statistical procedures allowing the separation of pure and joint contribution of the factors driving the observed spatial patterns.

Inside Front Cover - Aitor Ameztegui1; Lluís Coll; Lluís Brotons; Josep M. Ninot (Global Ecology and Biogeography, 2016)

Land‐use legacies rather than climate change are driving the recent upward shift of the mountain tree line in the P yrenees - Aitor Ameztegui; Lluís Coll; Lluís Brotons; Josep M. Ninot (Global Ecology and Biogeography, 2016)
Aim To assess the effects of climate change, past land uses and physiography on the current position of the tree line in the C atalan P yrenees and its dynamics between 1956 and 2006. Location More than 1000 linear kilometres of sub‐alpine tree line in the C atalan P yrenees (north‐east S pain) Methods Using aerial photographs and supervised classification, we reclassified the images into a binary raster with ‘tree’ and ‘non‐tree’ values, and determined canopy cover in 1956 and 2006. We then determined the change in position of the tree line between 1956 and 2006 based on changes in forest cover. We used the distance from the position of the tree line in 1956 to the theoretical potential tree line – determined from interpretation of aerial photographs, identifying the highest old remnants of forest for homogeneous areas of the landscape in terms of bioclimatic conditions, bedrock, landform and exposure – as a surrogate of intensity of past land uses. Results Our analyses showed that the P yrenean tree line has moved upwards on average almost 40 m (mean advance ± SE : 35.3 ± 0.5 m, P P Main conclusions Our results stress the impact of the cessation of human activity in driving forest dynamics at the tree line in the C atalan P yrenees, and reveal a very low or even negligible signal of climate change in the study area.

Both Volatiles and Cuticular Plant Compounds Determine Oviposition of the Willow Sawfly Nematus oligospilus on Leaves of Salix spp. (Salicaceae) - Celina L. Braccini; Andrea S. Vega; M. Victoria Coll Aráoz; Peter E. Teal; Teresa Cerrillo; Jorge A. Zavala; Patricia C. Fernandez (Journal of Chemical Ecology, 2015)

Growth and yield of mixed versus pure stands of Scots pine (Pinus sylvestris L.) and European beech (Fagus sylvatica L.) analysed along a productivity gradient through Europe - H. Pretzsch; M. del Río; Ch. Ammer; A. Avdagic; I. Barbeito; K. Bielak; G. Brazaitis; L. Coll; G. Dirnberger; L. Drössler; M. Fabrika; D. I. Forrester; et al. (European Journal of Forest Research, 2015)

Modelling dynamic ecosystems: venturing beyond boundaries with the Ecopath approach - M. Coll; E. Akoglu; F. Arreguín-Sánchez; E. A. Fulton; D. Gascuel; J. J. Heymans; S. Libralato; S. Mackinson; I. Palomera; C. Piroddi; L. J. Shannon; J. Steenbeek; et al. (Reviews in Fish Biology and Fisheries, 2015)

Risk of intrauterine growth restriction among HIV-infected pregnant women: a cohort study - M. López; M. Palacio; A. Goncé; S. Hernàndez; F. J. Barranco; L. García; M. Loncà; J. O. Coll; E. Gratacós; F. Figueras (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Ontogeny and total sugar content of yacon tuberous roots and other three Smallanthus species (Heliantheae, Asteraceae), insights on the development of a semi-domesticated crop - María V. Coll Aráoz; Alejandra M. Kortsarz González; María I. Mercado; Graciela I. Ponessa; Alfredo Grau; César A. N. Catalán (Genetic Resources and Crop Evolution, 2014)

Exploring Patterns of Seafood Provision Revealed in the Global Ocean Health Index - Kristin M. Kleisner; Catherine Longo; Marta Coll; Ben S. Halpern; Darren Hardy; Steven K. Katona; Frédéric Le Manach; Daniel Pauly; Andrew A. Rosenberg; Jameal F. Samhouri; Courtney Scarborough; U. Rashid Sumaila; et al. (Ambio, 2013)

An ocean observation system for monitoring the affects of climate change on the ecology and sustainability of pelagic fisheries in the Pacific Ocean - Simon J. Nicol; Valerie Allain; Graham M. Pilling; Jeff Polovina; Marta Coll; Johann Bell; Paul Dalzell; Peter Sharples; Robert Olson; Shane Griffiths; Jeffrey M. Dambacher; Jock Young; et al. (Climatic Change, 2013)

Matrix metalloproteinase expression and activity in trophoblast-decidual tissues at organogenesis in CF-1 mouse - Vanina Fontana; Tamara A. Coll; Cristian M. A. Sobarzo; Leticia Perez Tito; Juan Carlos Calvo; Elisa Cebral (Journal of Molecular Histology, 2012)

Serotype 3 is a common serotype causing invasive pneumococcal disease in children less than 5 years old, as identified by real-time PCR - L. Selva; P. Ciruela; C. Esteva; M. F. Sevilla; G. Codina; S. Hernandez; F. Moraga; J. J. García-García; A. Planes; F. Coll; I. Jordan; N. Cardeñosa; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Aspirin induces apoptosis in human leukemia cells independently of NF-κB and MAPKs through alteration of the Mcl-1/Noxa balance - Daniel Iglesias-Serret; Maria Piqué; Montserrat Barragán; Ana M. Cosialls; Antonio F. Santidrián; Diana M. González-Gironès; Llorenç Coll-Mulet; Mercè de Frias; Gabriel Pons; Joan Gil (Apoptosis, 2010)

Biological patterns and ecological indicators for Mediterranean fish and crustaceans below 1,000 m: a review - F. Sardà; J. B. Company; G. Rotllant; M. Coll (Reviews in Fish Biology and Fisheries, 2009)

A simple equation for determining sea surface emissivity in the 3–15 µ m region - R. Niclòs; V. Caselles; E. Valor; C. Coll; J. M. Sánchez (International Journal of Remote Sensing, 2009)

Hyperspectral indices for detecting changes in canopy reflectance as a result of underground natural gas leakage - M. F. Noomen; K. L. Smith; J. J. Colls; M. D. Steven; A. K. Skidmore; F. D. Van Der Meer (International Journal of Remote Sensing, 2008)

Evaluation of the B ‐method for determining actual evapotranspiration in a boreal forest from MODIS data - J. M. Sánchez; V. Caselles; R. Niclós; E. Valor; C. Coll; T. Laurila (International Journal of Remote Sensing, 2007)

The Systemic Absorption of Etoposide after Intravaginal Administration in Patients with Cervical Intraepithelial Lesions Associated with Human Papillomavirus Infection - P. García-López; M. Coll; E. Cervera; L. Reyes-Vermot; M. A. Torres; G. Ábrego-Pérez; A. I. Hernández-Pájaro; G. Castañeda-Hernandez; A. Mohar-Betancourt; A. Meneses (Pharmaceutical Research, 2006)

A Facility to Investigate Effects of Elevated Soil Gas Concentration on Vegetation - K. L. Smith; J. J. COLLS; M. D. Steven (Water, Air, & Soil Pollution, 2005)

Medical speciality and pattern of medicines prescription - A. Vallano; E. Montan; J. M. Arnau; X. Vidal; C. Pallars; M. Coll; J. R. Laporte (European Journal of Clinical Pharmacology, 2004)

Improvement of Transfection Efficiency of Epithelioma Papulosum Cyprini Carp Cells by Modification of Cell Cycle and Use of an Optimal Promoter - A. Rocha; S. Ruiz; J. M. Coll (Marine Biotechnology, 2004)

Effect of Spirostane Analogues of Brassinosteroids on Callus Formation and Plant Regeneration in Lettuce (Lactuca sativa) - M. Núñez; W.J. Siqueira; M. Hernández; M.A.T. Zullo; C. Robaina; F. Coll (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Application of Inducible and Targeted Gene Strategies to Produce Transgenic Fish: A Review - A. Rocha; S. Ruiz; A. Estepa; J. M. Coll (Marine Biotechnology, 2004)

Induction of Oxidative Stress in the Red Macroalga Gracilaria tenuistipitata by Pollutant Metals - J. Colln; E. Pinto; M. Pedersn; P. Colepicolo (Archives of Environmental Contamination and Toxicology, 2003)

Detection of QTL affecting fatty acid composition in the pig - Alex Clop; Cristina Ovilo; Miguel Perez-Enciso; Albert Cercos; Anna Tomas; Ana Fernandez; Agustina Coll; Josep M. Folch; Carmen Barragan; Isabel Diaz; Maria A. Oliver; Luis Varona; et al. (Mammalian Genome, 2003)

Improvement of DNA transfection with cationic liposomes - A. Rocha; S. Ruiz; J. M. Coll (Journal of Physiology and Biochemistry, 2002)

Transfection of epithelioma papulosum cyprini (EPC) carp cells - A. Lopez; M. Fernandez-Alonso; A. Rocha; A. Estepa; J.M. Coll (Biotechnology Letters, 2001)

Abstracts of Presentations at the 18th Conference of the Entomological Society of Israel - M. P. Pener; L. Anshelevich; E. Dunkelblum; M. Hard; A. Harari; D. Gordon; M. Kehat; H. Reuveny; O. Akunis; D. Oppenheim; E. Dunkelblum; Acta Rafaeli; et al. (Phytoparasitica, 2001)

Abstracts - Danuta Babula; Malgorzata Ruminska; Jan Sadowski; Josep M. Folch; Ramona Natacha Pena; Agustina Coll; Armand Sánchez; James M. H. Kijas; Leif Andersson; Dušan Kordiš; Franc Gubenšek; Gregor Majdič; et al. (Pflügers Archiv - European Journal of Physiology, 2000)

Abstracts of papers presented at the 16th conference of the Entomological Society of Israel Research on thrips in Israel Dedicated to the Memory of Prof. E. Rivnay on the 100th Anniversary of his Birth - M. Wysoki; M. Wysoki; M. Klein; M. Davidovich; R. Shaked; K. Rosenfeld; E. Pressman; Phyllis G. Weintraub; A. R. Horowitz; Sophia Kleitman; R. Azari; Leah Tsror; et al. (Phytoparasitica, 1999)

Induced fusion of VHSV persistently infected fish cells - M. Fernandez‐Alonso; J. M. Coll (Journal of Fish Diseases, 1999)

Isolation, sequencing and relative quantitation by fluorescent-ratio PCR of feline β-lactoglobulin I, II, and III cDNAs - Ramona N. Pena; Armand Sánchez; Agustina Coll; Josep M. Folch (Mammalian Genome, 1999)

Avocado shoot culture, plantlet development and net CO2 assimilation in an ambient and CO2 enhanced environment - Witjaksono; Bruce A. Schaffer; Angel M. Colls; Richard E. Litz; Pamela A. Moon (In Vitro Cellular & Developmental Biology - Plant, 1999)

A model to study fish DNA immersion vaccination by using the green fluorescent protein - M. Fernandez‐Alonso; F. Alvarez; A. Estepa; R. Blasco; J. M. Coll (Journal of Fish Diseases, 1999)

G disulphide bond native conformation is required to elicit trout neutralizing antibodies against VHSV - M. Fernandez‐Alonso; F. Alvarez; A. Estepa; J. M. Coll (Journal of Fish Diseases, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Relative frequencies of cystic fibrosis mutations in The Netherlands as an illustration of significant regional variation in a small country - J. M. Colle; Hendrik G. de Vries; Hans Scheffer; Dicky J. J. Halley; Leo P. ten Kate (Human Genetics, 1998)

Facilitatory effects of thalamic reticular nucleus lesions on two-way active avoidance in rats - N. Tenas-Huerga; M. Coll-Andreu; G. Guillazo-Blanch; I. Morgado-Bernal; M. Mart-Nicolovius (Experimental Brain Research, 1998)

Synthetic peptides from the heptad repeats of the glycoproteins of rabies, vesicular stomatitis and fish rhabdoviruses bind phosphatidylserine - J. M. Coll (Archives of Virology, 1997)

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

Chromosome segregation in a man heterozygous for a pericentric inversion, inv(9)(p11q13), analyzed by using sperm karyotyping and two-color fluorescence in situ hybridization on sperm nuclei - P. Colls; J. Blanco; O. Martínez-Pasarell; F. Vidal; J. Egozcue; C. Márquez; M. Guitart; C. Templado (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Expression of caprine β-lactoglobulin in the milk of transgenic mice - Elena Ibanez; Josep M. Folch; Francesca Vidal; Agustina Coll; Josep Santalo; Josep Egozcue; Armand Sanchez (Transgenic Research, 1997)

The glycoprotein G of rhabdoviruses - J. M. Coll (Archives of Virology, 1995)

Neutralizing-enhancing monoclonal antibody recognizes the denatured glycoprotein of viral haemorrhagic septicaemia virus - F. Sanz; J. M. Coll (Archives of Virology, 1992)

The free nucleocapsids of the viral haemorrhagic septicaemia virus contain two antigenically related nucleoproteins - B. Basurco; F. Sanz; M. A. Marcotegui; J. M. Coll (Archives of Virology, 1991)